The Usefulness of the Pressure Algometer in the Diagnosis and Treatment of Orofacial Pain Patients: A Systematic Review - Agata Kamińska; Bartosz Dalewski; Ewa Sobolewska (Occupational Therapy International, 2020)
Study Design. Data were obtained from PubMed, Dentistry and Oral Sciences Source, ProQuest, Scopus, Medline (EBSCO), and ScienceDirect databases. Literature search was performed from 1 December 2017 through 12 January 2018. The titles and abstracts from electronic search results were screened for keywords and evaluated by two observers, with the following inclusion criteria: published since 1997, written in English, and encompassing human research. Exclusion criteria were as follows: articles published earlier than 1997, not written in English, animal studies, studies with the use of medicaments, and articles examining receptor interactions. Objectives. The pressure pain threshold (PPT) may be an efficient approach to screen and evaluate orofacial pain. However, the results of previous PPT studies have varied greatly. The aim of this paper was to determine whether the PPT is an efficient approach for screening and evaluating orofacial pain. Methods. The search yielded 123 articles. After removal of duplicates and screening of abstracts, 32 articles were selected for further evaluation. The Cochrane Collaboration tool for assessing the risk of bias was used for the evaluation of the studies. Results. The studies covered a total of 4403 adult patients, aged 16-62, and 30 children. The studies investigated the reliability and validity of the PPT (measured by a pressure algometer) in TMD patients. The PPT was investigated in relation to headache, menstrual cycle, oral contraception, occlusal interference, and occlusal appliances. Generally, the risk of bias was low to unclear. Some structural limitations were inherent in the studies, such as small samples and short duration of the testing involved. Also, the analyzed studies lacked consistency in study design and patient management. Pressure increase values differed from 20 kPa/s to 50 kPa/s and from 0.5 kg/cm2/s to 2 kg/cm2/s. Descriptions of the PPT examination points also varied, from very precise and repeatable to a simple listing of anatomical points. The number of measurements varied from 1 to 5 at each visit. The intervals ranged from 5 seconds to 15 minutes. However, some studies confirmed that the pressure algometer is an effective tool for determining the source of orofacial pain. Conclusions. Based on the analyzed articles, the authors argue that the PPT is not an efficient approach for screening and evaluating orofacial pain. What is more, it should not be used as the only diagnostics tool for patients with orofacial pain. Importantly, however, additional factors should be considered in the future for the evaluation of the PPT, including body symmetry and posture, hormone levels and the menstrual phase in women, and the use of medications and its influence on the PPT. Further clinical trials should also be performed on the PPT, examining head and neck pain patients, with more precise study design and larger samples.